Hak asasi manusia dalam peradilan internasional: Tantangan kontemporer - kamilia, syalaisha Kholila (Maliki Interdisciplinary Journal, 2024)
Upholding human rights (HAM) in international justice is an important issue in the era of globalization. Despite a strong international legal framework, such as the Universal Declaration of Human Rights and various international conventions, complex and diverse contemporary challenges continue to confront the international justice process. Some of these challenges include political resistance from countries that do not recognize the authority of international courts, as well as the emergence of new issues such as cybersecurity, climate change, and new technologies that demand rapid adaptation from international courts. In facing these challenges, close collaboration between states, international organizations, civil society and human rights institutions is necessary to ensure universal and inclusive human rights protection.